2003
DOI: 10.1046/j.1538-7836.2003.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent signaling from Gαq- and Gαi-coupled pathways is essential for agonist-induced αvβ3 activation on human platelets

Abstract: Summary. The integrin avb3 mediates platelet adhesion to the matrix protein osteopontin and likely is the predominant integrin mediating platelet adhesion to the matrix protein vitronectin. To address the mechanism that regulates avb3 activity in platelets, we measured the effect of the P2Y 1 antagonist adenosine 3 H -phosphate-5 H -phosphate (A3P5P) and the P2Y 12 antagonist AR-C66096 on ADP-stimulated platelet adhesion to osteopontin and vitronectin. Each antagonist completely inhibited platelet adhesion, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…However, whether platelet adhesion is due exclusively to the integrin-clustering that accompanies ligand binding or results from an agonist-induced increase in ␣ v ␤ 3 affinity for OPN was not clear before the results presented in this paper. Although we have found that perturbing the conformation of the extracellular portion of ␣ v ␤ 3 with either dithiothreitol or Mn 2ϩ also induces platelet adhesion to OPN (13), suggesting that a conformational change in ␣ v ␤ 3 is sufficient to support adhesion, the inability to detect binding of the ligand-mimetic ␣ v ␤ 3 antibody WOW-1 to thrombin-stimulated platelets (15) suggests that this might not be the case. Accordingly, we applied laser tweezers technology to this question, much as we had used the technology to study the interaction of fibrinogen to platelet ␣ IIb ␤ 3 (8).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…However, whether platelet adhesion is due exclusively to the integrin-clustering that accompanies ligand binding or results from an agonist-induced increase in ␣ v ␤ 3 affinity for OPN was not clear before the results presented in this paper. Although we have found that perturbing the conformation of the extracellular portion of ␣ v ␤ 3 with either dithiothreitol or Mn 2ϩ also induces platelet adhesion to OPN (13), suggesting that a conformational change in ␣ v ␤ 3 is sufficient to support adhesion, the inability to detect binding of the ligand-mimetic ␣ v ␤ 3 antibody WOW-1 to thrombin-stimulated platelets (15) suggests that this might not be the case. Accordingly, we applied laser tweezers technology to this question, much as we had used the technology to study the interaction of fibrinogen to platelet ␣ IIb ␤ 3 (8).…”
Section: Discussionmentioning
confidence: 82%
“…are likely similar (13), sites at which OPN and fibrinogen bind to these integrins undoubtedly differ. Thus, whereas fibrinogen binds to ␣ IIb ␤ 3 via the carboxyl terminus of its ␥ chain (26), OPN binding to ␣ v ␤ 3 is mediated by its RGD motif (12), accounting, at least in part, for the measured differences in OPN and fibrinogen binding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations